The influence of Gd2O3 on shielding, thermal and luminescence properties of WO3–Gd2O3–B2O3 glass for radiation shielding and detection material. (January 2022) - Kaewnuam, E.; Wantana, N.; Tanusilp, S.; Kurosaki, K.; Limkitjaroenporn, P.; Kaewkhao, J.
Abstract: The physical, structural, optical, shielding, thermal and luminescence properties of WO3 -Gd2 O3 –B2 O3 glasses were studied in this work. The effect of WO3 replacement by Gd2 O3 on radiation shielding and radiation detection potential was evaluated. The glass density increases with increasing Gd2 O3 concentration and the maximum value is 5.97 g/cm 3 . The FTIR and XRD result confirm that the trigonal BO3, tetrahedral BO4 and tungsten complex are the main chemical groups and coorperate into the amorphous structure of glass. The optical absorption spectra exhibit the absorbance of glasses in ultraviolet and visible light region. The shielding parameters of glasses, such as mass attenuation coefficient, effective atomic number, electron density and half value layer, were investigated theoretically and experimentally. They perform a small degradation of shielding property by increasing Gd2 O3 content. There is no obvious dependence of Gd2 O3 concentration on glass thermal conductivity and expansion. The strong photoluminescence of [WO6 ] 6- group with 524 nm occurred under its charge transfer excitation and under the energy transfer from excited Gd 3+ ion. In the radioluminescence, WGB glasses emitted the visible light with 562 nm based on the mixed emission from [WO6 ] 6- group and oxygen vacancy. The glass possesses the X-ray detection efficiency around 18.65% of BGO crystal. The WO3 –Gd2 O3 –B2 O3 glass with 17.5 and 27.5 mol% of Gd2 O3 is a promising γ-ray shielding material at room temperature and high temperature circumstance, respectively and one with 25 mol% of Gd2 O3 owns the attractive potential for the X-ray radiation detection applications. Highlights: The self-luminescence of WO3 –Gd2 O3 –B2 O3 glass. X-ray detection ability. High radiation shielding quality compared to shielding concrete and Schott's glass. High-density glass.